Syzygium aromaticum Extracts as a Potential Antibacterial Inhibitors against Clinical Isolates of Acinetobacter baumannii: An In-Silico-Supported In-Vitro Study - Abdelhamed Mahmoud; Magdy M. Afifi; Fareed El Shenawy; Wesam Salem; Basem H. Elesawy (MDPI AG, 2021)
Imipenem is the most efficient antibiotic against Acinetobacter baumannii infection, but new research has shown that the organism has also developed resistance to this agent. A. baumannii isolates from a total of 110 clinical samples were identified by multiplex PCR. The antibacterial activity of Syzygium aromaticum multiple extracts was assessed following the GC-Mass spectra analysis. The molecular docking study was performed to investigate the binding mode of interactions of guanosine (Ethanolic extract compound) against Penicillin- binding proteins 1 and 3 of A. baumannii. Ten isolates of A. baumannii were confirmed to carry recA and iutA genes. Isolates were multidrug-resistant containing blaTEM and BlaSHV. The concentrations (0.04 to 0.125 mg mL−1) of S. aromaticum ethanolic extract were very promising against A. baumannii isolates. Even though imipenem (0.02 mg mL−1) individually showed a great bactericidal efficacy against all isolates, the in-silico study of guanosine, apioline, eugenol, and elemicin showed acceptable fitting to the binding site of the A. baumannii PBP1 and/or PBP3 with highest binding energy for guanosine between −7.1 and −8.1 kcal/mol respectively. Moreover, it formed π-stacked interactions with the residue ARG76 at 4.14 and 5.6, Å respectively. These findings might support the in vitro study and show a substantial increase in binding affinity and enhanced physicochemical characteristics compared to imipenem.